THE CORRELATION BETWEEN GESTATION PERIOD AND ICTERUS NEONATORUM AT DR. H. ABDUL MOELOEK HOSPITAL, LAMPUNG, INDONESIA - Yetty Dwi Fara; Eka Nur Fitriana (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: One of the causes of perinatal or neonatal mortality is icterus neonatorum, which is the main cause of neonatal mortality of 20-40% of all deliveries. The emergency neonatal condition becomes the cause of occurrence of neonatal mortality is the increased levels of bilirubin in blood or icterus neonatorum, which 50% occur in infants with <36 weeks gestation (preterm). Aims: To analyze the correlation between the gestation period and icterus neonatorum, so it is supposed to reduce the incidence of icterus neonatorum. Methods: This research is quantitative approach with cross sectional design and analyses hypothesis used chi-square test. The sample of this study is 289 infants used simple random sampling technique and the lottery system. Data used secondary data from the medical record that collected through the checklist. Results: Most of the infants with gestation period <36 weeks experienced the icterus neonatorum (62.5%) and the result of the chi-square test is p-value = 0.000. Odd Ratio (OR) of this research is 7.805 it means that gestation period <36 weeks have risked eight times than infants with gestation period ≥36 weeks. Conclusion: Pregnancy with gestation period <36 weeks has more changes to deliver newborn with icterus neonatorum. Routinely and regularly Antenatal Care (ANC) expected to detect early preterm birth.